Pentingnya Pendidikan Seksualitas dalam Mencegah Kekerasan Seksual Terhadap Perempuan - Clara Amanda; Ade Adhari (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Sexual violence against women is a global problem that has a significant impact on the physical, mental and social impacts of victims. One of the root causes of sexual violence is a lack of knowledge about sexuality, the concept of consent, and an imbalance in gender norms. This research is aimed at analyzing the important role of sexuality education in preventing sexual violence against women at various levels of society. The legal research method aimed at is qualitative empirical, which integrates normative legal approaches with social law. This approach is stated as an effort to identify indicators of problems that may be related to the laws and regulations that apply to society. The research findings indicate that sexuality education plays a very crucial role in carrying out efforts to prevent sexual violence against women. By providing the public with an understanding of sexuality, consent, sexual rights and gender equality, this education can reduce incidents of sexual violence and create a society that is more aware and respectful of the rights of each individual. Although there are various challenges in implementation, collaboration between government, educational institutions, parents and communities can strengthen sexuality education as an effective means of preventing sexual violence.